Language picture of the world in the light of the problem of “language and culture” - Kiklewicz, Aleksander (Papers in Linguistics, 2021)
The article touches upon an important theoretical problem of modern anthropology of language, i.e. the connection of the category “language picture of the world” and the problem of relationships between language and culture. In contemporary ethnolinguistics, there is an idea that the language picture of the world is a continuation of culture, a manifestation of a special, “cultural” vision of the world. The author quotes arguments in line with which the language semantics and the culture-conditioned picture of the world coincide only to some extent. It is shown that there are several spheres of language use in which the linguistic and cultural pictures of the world are opposed. The presented arguments are supported by examples from Russian and other Slavic languages.